Atención temprana de la violencia de pareja. Una propuesta desde la mediación familiar (2024)
Partner violence is the way to confront conflicts that arise within intimate relationships and current couples or those in the process of separation, exercised by men on women due to their gender status and that includes behaviors of physical, psychological, sexual abuse and other controlling behaviors or coercive threats, Puente et al. (2016).